Recent Advancements and Development in Nano-Enabled Agriculture for Improving Abiotic Stress Tolerance in Plants - Manzoor, Natasha; Ali, Liaqat; Ahmed, Temoor; Noman, Muhammad; Adrees, Muhammad; Shahid, Muhammad Shafiq; Ogunyemi, Solabomi Olaitan; Radwan, Khlode S. A.; Wang, Gang; Zaki, Haitham E. M. (Frontiers in Plant Science, 2022)
Abiotic stresses are the foremost limiting factors that adversely affect plant growth and crop productivity worldwide. Abiotic stresses, such as heavy metals, heat, drought, and salinity are major challenges various regions face. The plants response to such stresses is complex that results in different morphological, physiological and metabolism alterations. Over the past few decades, abiotic stresses have been managed through marker-assisted breeding, conventional breeding and genetic engineering approaches. As scientific technology has evolved, efficient strategies are required to cope with the harmful effects of abiotic stresses for sustainable agriculture systems. Recently, nanotechnology has emerged as a promising area of research with potential applications in agriculture, including mitigating the impacts of climate change, increasing nutrient utilization efficiency and abiotic stress management. Nanoparticles (NPs) has gained significant attention due to their low cost, eco-friendliness, unique physicochemical properties, high surface area to volume ratio, and improved plant productivity as nano fertilizers. Several studies have reported the potential role of NPs in abiotic stress management. This study aims to emphasize the role of NPs in managing abiotic stresses and growth promotion to develop a cost-effective and eco-friendly strategy for future agricultural sustainability.